Measuring restoration progress using pore- and surface-water chemistry across a chronosequence of formerly afforested blanket bogs. (1st August 2018) - Gaffney, Paul P.J.; Hancock, Mark H.; Taggart, Mark A.; Andersen, Roxane
Abstract: During the restoration of degraded bogs and other peatlands, both habitat and functional recovery can be closely linked with nutrient cycling, which is reflected in pore- and surface-water chemistry. Several peatland restoration studies have shown that the time required for recovery of target conditions is slow (>10 years); for heavily-impacted, drained and afforested peatlands of northern Scotland, recovery time is unknown. We monitored pore- and surface-water chemistry across a chronosequence of formerly drained, afforested bog restoration sites spanning 0–17 years, using a space-for-time substitution, and compared them with open blanket bog control sites. Our aims were to measure rate of recovery towards bog conditions and to identify the best suite of water chemistry variables to indicate recovery. Our results show progress in recovery towards bog conditions over a 0–17 year period post-restoration. Elements scavenged by trees (Mg, Na, S) completely recovered within that period. Many water chemistry variables were affected by the restoration process itself, but recovered within 11 years, except ammonium (NH4 + ), Zn and dissolved organic carbon (DOC) which remained elevated (when compared to control bogs) 17 years post restoration. Other variables did not completely recover (water table depth (WTD), pH), exhibiting what we term "legacy" effects of drainage and afforestation. Excess N and a lowered WTD are likely to slow the recovery of bog vegetation including key bog plants such as Sphagnum mosses. Over 17 years, we measured near-complete recovery in the chemistry of surface-water and deep pore-water but limited progress in shallow pore-water. Our results suggest that at least >17 years are required for complete recovery of water chemistry to bog conditions. However, we expect that newer restoration methods including conifer harvesting (stem plus brash) and the blocking of plough furrows (to increase the WTD) are likely to accelerate the restoration process (albeit at greater cost); this should be evaluated in future studies. We conclude that monitoring pore- and surface-water chemistry is useful in terms of indicating recovery towards bog conditions and we recommend monitoring WTD, pH, conductivity, Ca, NH4 +, phosphate (PO4 3− ), K, DOC, Al and Zn as key variables. Graphical abstract: Highlights: After restoration, water chemistry progressed toward bog conditions over 17 years. pH, NH4 + and WTD had not recovered completely within 17 years. PO4 3− and K were released post-restoration, but levels recovered within 11 years. We recommend monitoring WTD, pH, conductivity, Ca, NH4 +, PO4 3−, K, DOC, Al and Zn.